Association Between Long Boarding Time in the Emergency Department and Mortality at King Abdul-Aziz Hospital - Bakhribah, Ahmad (Journal of King Abdulaziz University: Medical Sciences, 2023)
Objective: To assess the association of boarding time in the ED and increased patient mortality at King Abdul-Aziz University Hospital in Jeddah, Saudi Arabia. Methods: A retrospective study was conducted on 28,066 patients admitted through the ED and discharged from January to December 2019 at King Abdul-Aziz University Hospital in Jeddah, Saudi Arabia. Data on patients’ demographics, age, nationality, arrival method, eligibility, triage level, outcome, and fate (death or alive) were collected from medical records. Results: This study found a strong link between patient mortality and boarding time, with patients who died experiencing significantly longer boarding times than those who survived. The average boarding time for those who died was more than 12 hours, compared to only 2.2% of those who did not. Additionally, the death rate was higher among non-eligible and male patients, and patients with injuries or orthopedic diseases had notably higher percentages of more than 12 hours of boarding time. Both long boarding time and non-eligibility for management were risk factors for death among the patients studied. Conclusion: This paper highlights the impact of protracted boarding times on patient outcomes and emphasizes the urgent need to take immediate steps to decrease ED boarding.